A Simultaneous Scheme for Solving Systems of Inclusion and Equilibrium Problems in a Real Banach Space: Lateef Olakunle. Jolaoso, Ferdinard Udochukwu Ogbuisi, Olawale Kazeem Oyewole, Oluwatosin Temitope Mewomo, Prasit Cholamjiak - Team, Support (Thai Journal of Mathematics, 2021)
In this paper, we propose an iterative method for approximating a common zero of finite family of m-accretive operators and a common solution of finite family of equilibrium problems simultaneously in a real reflexive, strict convex and smooth Banach space. We prove a strong convergence theorem and also give some applications of our result to approximating solutions of other nonlinear problems in real Banach spaces. As a special case, we obtain a result for approximating the common zero of a finite family of m-accretive operators which is also a common solution of a finite family of equilibrium problems in a real reflexive, strictly convex and smooth Banach space.